Damage Occurrence under Dynamic Loading For Anisotropic Strain Rate Sensitive Materials - F. Lauro (Shock and Vibration, 1998)
A damage model is integrated into the explicit finite element framework to predict the damage evolution which occurrs under dynamic loading in the crash or stamping process. This damage model is based on the description of the growth, nucleation and coalescence of the microvoids. The microvoid growth is related to the plastic incompressibility equation. The microvoid nucleation is controlled by either the plastic strain or stress. The microvoid coalescence is described by a specific function. This damage process leads to the progressive loss of the structure stress carrying capacity. The ductile fracture occurs once it has vanished. The model is adapted to take the material behaviour anisotropy and damage anisotropy into account. The sensitivity of the damage evolution under dynamic loadings in the case of porous strain rate sensitive material is analysed using single tensile tests. Static and dynamic tensile tests of a notched specimen are performed. Influences of the strain rate and the shape of specimen on the failure mode and loss of the structure’s stress carrying capacity are shown.